Transcutaneous auricular vagus nerve stimulation alters cough sensitivity depending on stimulation parameters: potential implications for aspiration risk - Ng, Karen B.; Guiu Hernandez, Esther; Haszard, Jillian; Macrae, Phoebe; Huckabee, Maggie-Lee; Cakmak, Yusuf O. (Frontiers in Neuroscience, 2024)
Background Transcutaneous auricular vagus nerve stimulation (taVNS) is considered a safe and promising tool for limb rehabilitation after stroke, but its effect on cough has never been studied. It is known that the ear and larynx share vagal afferent pathways, suggesting that stimulating the ear with taVNS might have effects on cough sensitivity. The specific stimulation parameters used can influence outcomes. Objective To investigate the effect of various stimulation parameters on change in cough sensitivity, compared to the reference parameter of 25 Hz stimulation at the left concha (most commonly-used parameter for stroke rehabilitation). Design, setting, and participants: Randomized, single-blind, active-controlled, eight-period cross-over design conducted March to August 2022 at a New Zealand research laboratory with 16 healthy participants. Interventions All participants underwent eight stimulation conditions which varied by stimulation side (right ear, left ear), zone (ear canal, concha), and frequency (25 Hz, 80 Hz). Main outcome measures: Change in natural and suppressed cough threshold (from baseline to after 10 min of stimulation) assessed using a citric acid cough reflex test. Results When compared to the reference parameter of 25 Hz stimulation at the left concha, there was a reduction in natural cough threshold of −0.16 mol/L for 80 Hz stimulation at the left canal (p = 0.004), indicating increased sensitivity. For the outcome measure of suppressed cough threshold, there was no significant effect of any of the stimulation conditions compared to the active reference. Conclusion Since stroke patients often have cough hyposensitivity with resulting high risk of silent aspiration, using 80 Hz taVNS at the left canal may be a better choice for future stroke rehabilitation studies than the commonly used 25 Hz taVNS at the left concha. Treatment parameters should be manipulated in future sham-controlled trials to maximize any potential treatment effect of taVNS in modulating cough sensitivity. Clinical trial registration ACTRN12623000128695.